PELATIHAN DAN BIMBINGAN KORESPONDENSI BISNIS DI BIDANG HOME INDUSTRI KULINER PAWON BUCI MALANG - Ellyn Eka Wahyu; Yekie Senja Oktora; Siti Nurbaya; Joni Dwi Pribadi; Achmad Suyono (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2021)
Pengabdian Kepada Masyarakat (PkM) in 2021, was carried out to provide training and guidance to mothers in the area around Pawon Buci Malang on Business Correspondence to help promote and market products from Pawon Buci Malang. The method used by the PkM Implementation Team is to provide an explanation of the meaning of letters, understanding of business correspondence, the importance of correspondence (especially during the Covid 19 Pandemic), requirements for a good letter, function of letters, language of letters, nature of business letters, form of letters, sections -Department of Letters, Sales Methods - Direct Sales, Kinds of Letters (Introduction Letters, Offer Letters, Order Acceptance Letters, Order Confirmation Letters, Order Rejection Letters). This PkM activity received high enthusiasm from the participants. The enthusiasm was evidenced by the completeness of the 5 participants who listened carefully and actively from the beginning to the end of the activity. The PkM Implementation Team concluded that all participants were able to put the results of the training into practice by being able to write the necessary documents to promote and market Pawon Buci products.